Carrion flies as sentinels for monitoring lagovirus activity in Australia. Issue 5 (10th June 2019) - Hall, Robyn N.; Huang, Nina; Roberts, John; Strive, Tanja
Abstract: Lagoviruses are an essential tool for managing wild rabbit populations in Australia. Our understanding of lagovirus epidemiology in Australia currently depends on members of the public submitting liver samples from dead lagomorphs (i.e. rabbits and hares) through a monitoring program called Rabbitscan. However, many wild lagomorphs die in inaccessible locations or are scavenged before sampling can occur, leading to considerable sampling bias. In this study, we screened field‐caught carrion flies for the presence of lagoviruses to monitor virus circulation patterns in the landscape, with an aim to establish a less biased epidemiological surveillance tool. Carrion flies were collected from two study sites over a 22‐month period and these samples were used to optimize and validate molecular testing methods in this sample type for the currently circulating lagovirus variants. Virus was clearly detectable in field‐caught carrion flies using optimized SYBR‐green RT‐qPCR and RT‐PCR assays. However, variant identification was frequently hindered by the low virus loads present in carrion fly samples and spurious RT‐PCR amplification. This was overcome by frequent sampling, which effectively acts as replicate sampling to verify inconclusive results. There was generally good correlation between virus detections and variant identification in carrion flies and in samples recovered from wild lagomorphs. The methods reported here provide an additional surveillance tool to monitor lagovirus spread and circulation at a landscape scale, which in turn can help to guide more effective rabbit management programs.